2002
DOI: 10.1046/j.1468-0734.2002.00057.x
|View full text |Cite
|
Sign up to set email alerts
|

STEM CELL TRANSPLANTATIONFOR LEUKEMIAS FOLLOWING MYELODYSPLASTIC SYNDROMESOR SECONDARYTO CYTOTOXIC THERAPY

Abstract: Two main forms of therapy-related myelodysplastic syndrome and acute myeloid leukemia (t-MDS/AML) have been recognized. The most frequent type, occurring after treatment with alkylating agents, is characterized by abnormalities of chromosomes 5 and/or 7 and t-MDS/AML following treatment with topoisomerase II inhibitors and is associated with molecular aberrations of MLL (11q23) and AML-1 (21q22). Individuals with certain polymorphisms associated with impaired detoxification of cytotoxic agents have an increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2003
2003
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 78 publications
0
6
0
2
Order By: Relevance
“…This suggests a distinct set of repair mechanisms is used by early pluripotent cells capable of long-term proliferation and differentiation. Inversions of MLL are rarely associated with t-AML with only a single case reported in the literature (49). In this case the long latency (6 yr persistence of a clone with inv 11 in the bone marrow before development of t-AML) suggests a benign character of this genetic lesion and requirement of other collaborating mutations (49).…”
Section: Discussionmentioning
confidence: 99%
“…This suggests a distinct set of repair mechanisms is used by early pluripotent cells capable of long-term proliferation and differentiation. Inversions of MLL are rarely associated with t-AML with only a single case reported in the literature (49). In this case the long latency (6 yr persistence of a clone with inv 11 in the bone marrow before development of t-AML) suggests a benign character of this genetic lesion and requirement of other collaborating mutations (49).…”
Section: Discussionmentioning
confidence: 99%
“…Although present data suggests that the initial response rates of most cases of this type of therapy-related leukemia to intensive initial chemotherapy is comparable to those of primary acute leukemia of the corresponding type, the long-term follow-up data to predict the ultimate survival in these patients is insufficient (184,206,208). de Witte et al (211) suggested that patients who attain a polyclonal and/or a cytogenetic complete remission may be candidates for autologous stem cell transplantation, but for the remaining patients allogeneic stem cell transplantation from a histocompatible sibling or an alternative donor is the best curative option at present (211,212).…”
Section: Therapy-related Acute Leukemiamentioning
confidence: 80%
“…In the uncommon cases where ALL is observed, the most frequent cytogenetic abnormality is t(4;11)(q21;q23) (204). The following are regarded as good risk cytogenetic features: t(15;17); t(18;21) and inv (16) (211). Although present data suggests that the initial response rates of most cases of this type of therapy-related leukemia to intensive initial chemotherapy is comparable to those of primary acute leukemia of the corresponding type, the long-term follow-up data to predict the ultimate survival in these patients is insufficient (184,206,208).…”
Section: Therapy-related Acute Leukemiamentioning
confidence: 99%
“…Múltiples estudios han demostrado que el principal factor pronóstico para conseguir la curación de la enfermedad es la ausencia de alteraciones citogenéticas desfavorables (5,81); en efecto, la RC a la quimioterapia sólo se da en el 13% de los pacientes con anormalidades del cromosoma 5 (del.5 o 5q-), independientemente de la presencia de anomalías en el cromosoma 7, en contraste con la respuesta en los pacientes con monosomía del cromosoma 7 o deleción del brazo largo (32%), con cromosomas extranumerarios (43%), o un cariotipo con otras anormalidades estructurales (65%). La presencia de las alteraciones citogenéticas favorables descritas en la LAM primaria, como t (15,17), t(8,21) e inv(16) es rara en las leucemias secundarias (5). En general, la mayor parte de estudios ha demostrado una tasa escasa de respuestas en los pacientes con alteraciones de los cromosomas 5 y 7, y tasas mayores en aquellos que presentan otras anormalidades cromosómicas.…”
Section: Leucemia Aguda Mieloideunclassified
“…Esta menor supervivencia parece deberse a un aumento de la mortalidad por el mayor número de recaídas y la mayor toxicidad del trasplante; son factores de peor pronóstico en estos pacientes la edad avanzada, el porcentaje de alteraciones citogenéticas, el número de blastos en médula ósea y la fibrosis de la médula, con la consiguiente menor reserva que favorece las muertes por toxicidad (4). A pesar de esos pobres resultados, el trasplante alogénico continúa siendo el tratamiento de elección (4)(5)(81)(82)(83). El uso de quimioterapia de inducción previo al trasplante no está claramente establecido: las tasas de RC son escasas (especialmente si hay alteraciones citogenéticas desfavorables), el riesgo de muerte durante la quimioterapia varía desde el 15 al 64% (4,81) (obviando a un porcentaje de pacientes del beneficio del trasplante) y no se ha podido demostrar que la realización del trasplante en RC mejore el pronóstico a largo plazo (4).…”
Section: Tabla Vunclassified